Earthquake risk embedded in property prices: Evidence from five Japanese cities - Masako Ikefuji; Roger J. A. Laeven; Jan R. Magnus; Yuan Yue (Tinbergen Institute, 2018)
We analyze the impact of short-run and long-run earthquake risk on Japanese property prices. We exploit a rich panel data set of property characteristics, ward attractiveness information, macroeconomic variables, seismic hazard data, and historical earthquake occurrences, supplemented with short-run earthquake probabilities that we generate from a seismic excitation model. We design a hedonic property price model that allows for probability weighting, employ a multivariate error components structure, and develop associated maximum likelihood estimation and variance computation procedures. We find that distorted short-run and long-run earthquake probabilities have a significantly negative impact on property prices. Our approach enables us to identify the total compensation for earthquake risk embedded in property prices and to decompose this into pieces stemming from short-run and long-run risk, and to further decompose this into objective and distorted risk components.
Keywords: R20; C33; D81; Q51; 330; Earthquake risk; House price; Seismic excitation; Probability weighting; Hedonic pricing; Multivariate error components